KARAKTERISASI EDIBLE COATING DARI MODIFIKASI PATI SAGU DENGAN METODA CROSS LINK (Jurnal Teknologi Industri Pertanian, 2019)
This study aims to make edible coating of native sago and modified sago by crosslink method and analyze  physicochemical properties. Analysis of swelling power, amylose content, fat content, protein content, degree of substitution, and gelatinization temperature have been performed against native starch and modified starch. Furthermore, the identification of organic compounds on natural starch and modified starch was carried out by Fourier Transform Infrared (FTIR) and structural morphology of starch using Scanning Electron Microscopy (SEM). Analysis of edible coatings includes mechanical properties, moisture content, and film morphology using SEM. The results showed that the starch modified by crosslink method has physicochemical properties better than the native starch.Keywords :cross link, sago, physicochemical property,  modified starch, edible coating